Knowledge and attitudes of health care workers about monkeypox virus infection in Southern Italy - Miraglia del Giudice, Grazia; Della Polla, Giorgia; Folcarelli, Lucio; Napoli, Annalisa; Angelillo, Italo Francesco; , The Collaborative Working Group; Longanella, Walter; Mensorio, Mario Massimo; Cantore, Federica (Frontiers in Public Health, 2023)
Background This present survey sought to investigate the level of knowledge and the attitudes pertaining the monkeypox (mpox) virus infection among a sample of health care workers (HCWs) in Italy, as well as the possible role of different factors on these outcomes. Methods The cross-sectional survey was performed from July through October, 2022 at four randomly selected hospitals located in Southern Italy. Results The questionnaire was completed by 421 HCWs, for an overall 59% response rate. Less than two-thirds were able to define the disease and the correct answer of the transmission mechanisms ranged from 22.8% for contact with contaminated objects to 75.8% through close contact with body fluids. Only 4% and 12.8% indicated HCWs and elderly/frail/people with underlying immune deficiencies as risk groups. The mean overall score of the knowledge assessment on mpox was 3.4 (0–9). The multivariate logistic regression analysis showed that HCWs with a lower number of years of working experience and those who had acquired information about mpox from scientific journals were more likely to have a higher level of knowledge. The average score of the perception of the severity of the disease was 6.3. A similar score with a value of 6.1 has been observed for the statement that mpox is a serious problem for the population. Regarding the level of concern about contracting mpox, the mean score was 5.1. Only 10.5% reported that they feel that this disease can be prevented, with an overall mean score of 6.5. Almost all HCWs reported that they are still living as usual, with no modification of their behavior for fear of contracting the mpox. The results of the multivariate logistic regression model showed that women, HCWs with a higher level of knowledge about mpox, and those who needed additional information about mpox were more likely to have a higher level of perception of the severity of the disease. Conclusion This survey has demonstrated that HCWs had an unsatisfactory level of knowledge toward mpox and only nearly half showed positive attitudes. Strategic health training programs should be made so that knowledge can be acquired.